Weaving on the Edge: The Tradition of Jamu Laut as a Social Network Hub in Jaring Halus Village - Muhammad Alwi Yanda Sitompul Alwi; Sandi Perdana Perdana; Dinda Arini Simbolon Simbolon; Indri Fitriani Siregar Siregar (Journal of Sumatera Sociological Indicators, 2026)
The Jamu Laut tradition in Jaring Halus Village is generally understood as merely a cultural heritage, thus occurring within social dynamics that are often overlooked. This study aims to analyze the function of the Jamu Laut tradition in forming and maintaining social networks in coastal communities. The research employed a qualitative approach through a systematic literature review of various relevant secondary data sources. The results indicate that Jamu Laut functions as a social mechanism that contributes to maintaining social cohesion, strengthening the value of mutual cooperation (gotong royong), and supporting the community's adaptation to economic and environmental conditions. Within the framework of structural functionalism, this tradition fulfills the functions of integration, adaptation, goal achievement, and pattern maintenance, although in practice it undergoes adjustments along with social changes. These findings confirm that Jamu Laut not only possesses cultural values ​​but also plays a role in supporting the continuity of community social relations, although its contribution is contextual and dependent on local dynamic.